Housing equilibrium price framework for Malaysian middle Class group in affordable housing market - Ramli, Fazilah (2017)
Failure in getting housing equilibrium price for affordable housing market has become a hot topic that is often discussed in the press due to the imbalance between housing demanded and supplied. The basic purpose of the research was to investigate the relationship between macroeconomic housing demand and supply detenninant factors and affordable housing needs in Malaysia, and to dete1111ine the equilibrium house price for middle-class income in the affordable housing market. The research involved the development of theoretical framework by synthesising the models and framework developed by past researchers on the housing equilibrium price framework. It also uses time series analysis together with regression analysis to collect and analyse data. As initial, 371 respondents from household's side and 32 respondents from developer's side in Melaka Tengah were selected as samples as case study in Melaka. During data analysed, around 200 questionnaires from households and 32 questionnaires from developers can be used. The data was analysed using SPSS software to investigate the relationship between macroeconomic housing demand and supply determinant factors towards the needs f and supply of afordable housing market. From the investigation, current house price, monetary status and population changes are the most critical factors that lead to the needs of affordable housing supplies. Meanwhile, developers put the interest rate, government interventions and population changes as the catalyst to develop the affordable housing projects. On the other hand, the empirical data of housing prices are collected from NAPIC from 2006 to 2015. The equilibrium price calculated from the sales perfonnance within four quarter reported by NAPIC is examined using linear regression method. Based on these themes, the research contended that the housing equilibrium price can be achieved using empirical data from demand and supply with supported from current house price, monetary status and population changes the interest rate, government interventions and population changes. Hence, government is the key player and be a pulling effect in controlling the housing price by using the housing demand and supply determinant factor to create a win-win situation between middle-class income and housing developers.